2015
DOI: 10.1177/0194599815590107
|View full text |Cite
|
Sign up to set email alerts
|

Response to Dr Chung’s Question on Simulating the Nasal Cycle with Computational Fluid Dynamics

Abstract: I was pleased to read the interesting article by Patel and coauthors, "Simulating the Nasal Cycle with Computational Fluid Dynamics," published in your journal. 1 Decongestion of the nose is used as a way of stabilizing and evaluating nasal patency. 2 Nearly all patients feel patent nasal cavity after decongestion. The objective of this article was to develop a new method to quantify nasal surgery outcomes by simulating the nasal cycle to evaluate the exact condition of patients. Change in the thickness of tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The method requires the creation of multiple nasal cycle models for each surgical state (i.e., pre-surgery and post-surgery), running CFD simulations in each model, and fitting a curve to describe the relationship between flow variables and inferior turbinate thickness so that flow variables can be estimated at the mid-cycle. This method was previously applied to simulate the nasal cycle in two NAO patients and the results revealed that the nasal cycle can dramatically influence objective measures of surgical outcomes (Garcia et al, 2015a; Patel et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The method requires the creation of multiple nasal cycle models for each surgical state (i.e., pre-surgery and post-surgery), running CFD simulations in each model, and fitting a curve to describe the relationship between flow variables and inferior turbinate thickness so that flow variables can be estimated at the mid-cycle. This method was previously applied to simulate the nasal cycle in two NAO patients and the results revealed that the nasal cycle can dramatically influence objective measures of surgical outcomes (Garcia et al, 2015a; Patel et al, 2015). …”
Section: Introductionmentioning
confidence: 99%